Quantitative Analysis of Synthetic Food Dyes in Libyan Confectionery Using UV-Vis Spectroscopy - Najat Aburas; Aisha Mohammed (AlQalam Journal of Medical and Applied Sciences, 2025)
The use of synthetic colors as food colorants in confectionery is increasing despite the potential health risks associated with their consumption. They make foods and beverages more attractive and are often used as alternatives to natural colors due to their colorfastness, consistency, and low cost. Therefore, it is necessary to constantly monitor the concentrations of these dyes in food and confectionery due to their health-related concerns. The investigation was conducted using a quartz cell and distilled water as a solvent, over a wavelength range of 400 nm to 800 nm. Twelve hard candy samples were collected from the Libyan market, containing four colorants: Sunset Yellow (E110), Ponceau 4R (E124), Allura Red AC (E129), and Brilliant Blue (E133). The results showed that the concentrations of synthetic colorants in the candy samples ranged from 14.74 ± 0.69 mg/kg to 215.03 ± 6.42 mg/kg. Among the detected dyes, E110 was found in five samples, with concentrations ranging from 14.45 ± 0.68 mg/kg to 120.77 ± 3.91 mg/kg. E129 was present in multiple samples, with concentrations ranging from 43.28 ± 0.24 mg/kg to 215.03 ± 6.42 mg/kg. E133 was identified in four samples, with concentrations between 21.13 ± 1.12 mg/kg and 127.87 ± 0.64 mg/kg. All concentrations were below the Codex Alimentarius limit of 300 mg/kg. E124 was detected in two samples, with concentrations of 38.96 ± 0.78 mg/kg and 143.59 ± 4.25 mg/kg; one sample (9(124)) exceeded the permitted level of 100 mg/kg.